(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
It is studied that the TSK influence of cumene, CHP and OS-20 on initiation on the quickness of oxidation rate of reactions is studied. It is shown that in any case TSK displays an inhibitorating character. Kinetic parameters characterizing the inhibitor are measured. During the oxidation of cumene in the reaction RO2 + In→ROOH +In the temperature dependence of velocity constant is determined as: k7 = 4.49·108 exp(-5300/RT) L/mol·s.